PENERAPAN TEKA-TEKI SILANG SEBAGAI MEDIA PEMBELAJARAN BIOLOGI UNTUK SISWA KELAS X MA - Fathan, Asroh (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2021)
The purpose of this study is to increase students’ science learning outcome, students’ activities, teacher activities, and students’ response to use crossword puzzle media in the material of ecosystem changes. This study used classroom action research design which refers to Kemmis and Taggart teory with the subjects are tenth grade students MA Nurul Huda Kragan academic years 2018/ 2019. This study’s procedures consist of focusing problem, plan, act, observe, and reflect. The results this study are crossword puzzle media can increase students’ science learning outcome, students’ activities, teacher activities, and students’ response to use crossword puzzle media in the material of ecosystem changes is good. The result shows that students’ science learnig outcomes is 55,56 % at the first cycle and 94,4 % at the second cycle. Increasing students’ activities is 14 % based on students’ activities 24 % at the first cycle and 38 % at the second cycle. The teacher activities increase 6,94 % from 25 % to 31,94 %. Students give good response after use crossword puzzle in study.